Efek Penurunan Kadar Glukosa Darah Rebusan Asparagus (Asparagus offi cinalis L.) Pada Mencit yang Diinduksi Aloksan - Rika Sari Dewi; Lestari Rahayu; Ni Made Dwi Sandhiutami; Sondang Khairani; Isti Atika (JURNAL ILMU KEFARMASIAN INDONESIA, 2021)
Diabetes mellitus characterized by hyperglycemia whereas the condition for high blood glucose. InIndonesia, there are a lot of medicinal plants that used as antidiabetic treatment. Medicinal plants are known have relatively few side eff ects compared to chemical based drugs. Asparagus (Asparagus offi cinalis L.) was reported to have fl avonoids and saponins compounds that could be functioned as antidiabetic. The aim of this research was to fi nd out the eff ect of boiled asparagus on blood glucose level in mice induced by Alloxan. This research used 30 male DDY strained mice, which were classifi ed into 6 groups, and each group consisted of 5 mice. These 6 groups were: normal control, negative control, positive control (Acarbose), the boiled asparagus with dose of 280, 560, and 840 mg/kgBW for 14 days. Blood glucose level of mice were observed on day-0, 8, 15, and 22. The results showed that Alloxan injection increased the level of blood glucose. Another result showed that boiled asparagus with dose of 280, 560 and 840 mg/kgBW reduced the level of blood glucose and the eff ect showed treatment groups doses of 560 dan 840 mg/kgBW had no signifi cantly diff erent with positive control group (Acarbose).